Ethics of Regional Leadership with Local Wisdom of Siri 'Na Pacce in Makassar Ethnic Society - Muhammad Nur Yamin; Novita Sari (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2020)
The study aims to determine the application of regional leadership ethics with local wisdom of Siri na Pacce Makassar ethnic community seen from the values contained in it, namely Appau Tojeng, Lambusu’, Jarrek, Sipakatau, Annyomba ri Karaeng La taala, and pacce. Continuity in the application of leadership values is reflected in the nature of leadership in the District Gowa Regency. The research method is descriptive qualitative, and the focus of research is on the leadership of the Regent of the Gowa Regency. Data collection techniques through interviews, observations, and documentation. Data on the research results were processed with the analysis technique model Miles and Huberman (2014). The results of the study show that local leadership ethics are still applied to a number of values, namely Appau Tojeng is applied through the union of words and actions taken; Jarrek is implemented through accountability for achieving the organization's vision and mission; Lambusu’ is applied through open information delivery; Sipakatau is implemented through the provision of benefits, Annyomba ri Karaeng Allah Taala is implemented through religious activities carried out within the scope of his administration; and pacce is applied through caring for employees and the community. Evidence of the importance of applying the ethical values of local cultural heritage to the organization's leadership, so that leaders, employees, and communities can create a good governance atmosphere